Kajian Pasang Surut Dengan Metode Least Square Di Perairan Kabupaten Bengkalis - Muhammad Yoganda; Andy Hendri; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Analysis of tidal components can be done with several methods, namely least square method, admiralty and so forth. The least square method is a tidal harmonic analysis method used to analyze and to predict tides in this research. Daily observation data of 15 days in each hour will be simulated against 158 variations of time using Hijri calendar, to find out the initial variation of observational data that best matches the tidal prediction in Bengkalis waters. The analysis was carried out using tidal data in the waters around the port of Roro Bengkalis. The analysis results show that the smallest average root mean square error (RMSE) value is on the initial variation of the 30th data for verification of the simulation data. The 30th days of the Hijri calendar is in the new moon phase.The tidal type of the location of the research based on the value of the Formzahl number was classified at the double mixed tide prevailing type (mixed tide prevailing semidiurnal).Keywords: formzahl, least square method, RMSE, tide prediction